Advanced Strategies to Tailor the Nucleation and Crystal Growth in Hybrid Halide Perovskite Thin Films - Kumar, Jitendra; Srivastava, Priya; Bag, Monojit (Frontiers in Chemistry, 2022)
Remarkable improvement in perovskite solar cell efficiency from 3.8 % in 2009 to 25.5 % today has not been a cakewalk. The credit goes to various device fabricating and designing techniques employed by the researchers worldwide. Even after tremendous research in the field, phenomena’s such as ion migration, phase segregation and spectral instability are not clearly understood till date. One of the widely used technique for the mitigation of ion migration is to reduce the defect density by fabricating high quality perovskite thin films. Therefore, understanding and controlling the perovskite crystallization and growth become inevitably crucial. Some of the latest methods attracting attention are controlling perovskite film morphology by modulating the coating substrate temperature, anti-solvent treatment and solvent engineering. Here, latest techniques of morphology optimization are discussed focusing the model of nucleation and growth. It can be noted that during the process of nucleation, the supersaturation stage can be induced faster by modifying the chemical potential of the system. The tailoring of Gibbs free energy and hence chemical potential using highly utilized techniques is summarized in this minireview. The thermodynamics of crystal growth, design and orientation by changing several parameters is highlighted.